To find the sum of two numbers in scientific notation, we need to ensure that both numbers have the same exponent.
6.3 times 10^3 can be expressed as 6.3 x 10^3
2.41 times 10^4 can be expressed as 0.241 x 10^5
Now, let's add the two numbers:
6.3 x 10^3 + 0.241 x 10^5 = 6.3 x 10^3 + 0.241 x 10^3 x 10^2 = 6.3 x 10^3 + 0.241 x 10^3 x 100
Simplifying further:
6.3 x 10^3 + 0.241 x 10^3 x 100 = 6.3 x 10^3 + 24.1 x 10^3
Combining like terms:
6.3 x 10^3 + 24.1 x 10^3 = (6.3 + 24.1) x 10^3 = 30.4 x 10^3
Finally, expressing the answer in scientific notation:
30.4 x 10^3 = 3.04 x 10^4
Therefore, the sum of 6.3 times 10^3 and 2.41 times 10^4 is 3.04 x 10^4.
what is the sum of 6.3 times 10^3 and 2.41 time 10^4? use scientific notation to express your answer
1 answer